2017
DOI: 10.1177/0300060517707901
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mortality in the emergency department at a university hospital in Pleven

Abstract: ObjectiveTo identify the demographic patterns of mortality, the time spent before death in the emergency department (ED), and the causes of fatal outcomes.MethodsWe performed a 5-year (01/01/2011 to 01/01/2016) retrospective analysis of all non-traumatic deaths in the ED of the UMHAT – Pleven. To extract the necessary information, we used the registers in the ED until the patients’ death.ResultsAmong 156,848 patients in the study period, 381 died and the mortality rate was 2.4/100000. The male:female ratio was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 8 publications
5
16
3
1
Order By: Relevance
“…Most of the patient deaths (88.1%) were caused by non-traumatic incidents that included heart diseases (50.0%), sudden death of uncertain cause (33.0%), chronic obstructive lung disease (2.6%), pneumonia (1.0%), cancer (0.5%), coronary artery disease (0.5%) and toxicity (0.5%). This is consistent with a recent study published in 2017, which reported that cardiovascular diseases are the leading cause of death in the emergency department, and is also consistent with our findings that reveal more than half of the patients died from heart diseases [23]. Moreover, a 9year follow-up study of emergency room users reported that the most dominant causes of death include circulatory system disorders, cancer, and violent events [24].…”
Section: Discussion:-supporting
confidence: 94%
“…Most of the patient deaths (88.1%) were caused by non-traumatic incidents that included heart diseases (50.0%), sudden death of uncertain cause (33.0%), chronic obstructive lung disease (2.6%), pneumonia (1.0%), cancer (0.5%), coronary artery disease (0.5%) and toxicity (0.5%). This is consistent with a recent study published in 2017, which reported that cardiovascular diseases are the leading cause of death in the emergency department, and is also consistent with our findings that reveal more than half of the patients died from heart diseases [23]. Moreover, a 9year follow-up study of emergency room users reported that the most dominant causes of death include circulatory system disorders, cancer, and violent events [24].…”
Section: Discussion:-supporting
confidence: 94%
“…With a mortality rate of 2.6/1,000 patients, our study reflected that of other available studies [7, 8, 27]. Though not reflective of the general population, this figure confirms what we already suspected that ED tends to the more vulnerable and sick; thus it comes as no surprise that the mean mortality age during the study period was 65.7 years, a figure also seen in the few other available comparative studies [8, 10–13].…”
Section: Discussionsupporting
confidence: 87%
“…The department is the backbone of the health facilities and the general public by providing the first line of care on arrival. In short, ED is the “shop window” of the health service [ 1 ].…”
Section: Introductionmentioning
confidence: 99%